2016
DOI: 10.14393/bj-v32n4a2016-29714
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of calcium and boron improves the spike fertily and yield of wheat

Abstract: Foliar applications of calcium (Ca) and boron (B) could improve the fertilization of flowers and enhance the wheat yield. The effects of foliar spray of Ca and B on plant growth, grain yield and yield components of wheat were investigated in this study. Treatments consisted of 0, 1.8, 3.6, and 7.2 L ha -1 application of chelated fertilizer containing 125 g L -1 of Ca and 6 g L -1 of B (Omega Cabor II ® ), divided into two spray, the first one at tillering and the second at early bloom. The results revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Also, Sahin et al, (2015) revealed that, calcium and boron treatments increased both the yield and concentrations of Ca and B in tomato leaves. Also, Zoz et al, (2016) indicated that, Ca and B foliar application stimulates growth, fertilization of flowers, number of fertile tillers and gave higher grains yield of wheat plants. Likewise, Maji et al, (2017) concluded that, the combined foliar spray of calcium as calcium chloride at 5 % and boron as borax at 0.25% could be practiced for good vegetative growth, fruits yield and quality of pomegranate (Punica granatum L.) cv.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sahin et al, (2015) revealed that, calcium and boron treatments increased both the yield and concentrations of Ca and B in tomato leaves. Also, Zoz et al, (2016) indicated that, Ca and B foliar application stimulates growth, fertilization of flowers, number of fertile tillers and gave higher grains yield of wheat plants. Likewise, Maji et al, (2017) concluded that, the combined foliar spray of calcium as calcium chloride at 5 % and boron as borax at 0.25% could be practiced for good vegetative growth, fruits yield and quality of pomegranate (Punica granatum L.) cv.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the application of cation nitrates led to a slightly positive response in grain yield of var. Vivendo despite a decrease in TKW, an effect probably due to improved spike and spikelet fertility with biofortification [58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Herath et al [22] recommended, in addition to basal lime application on pineapples, administering a calcium application six months after plantation (during the flowering stage) to improve the post-harvest quality and the product shelflife. Moreover, Zozo et al [23] showed that application of both calcium and boron sprays (the first at tillering and the second at early bloom) improves growth, flower fertilisation, and the number of fertile tillers of wheat plants, resulting in higher grain yield.…”
Section: Calcium Usementioning
confidence: 99%